The Role of Government Policies in Combating Unemployment in Palestinian Society - Iqnais, Lara; Iriqat, Ismail (The Arab Journal of Administration, 2025)
This study aims to identify the effectiveness and adequacy of government policies in combating the phenomenon of unemployment in Palestinian society, and to clarify the level of coordination between the competent authorities to combat unemployment. In addition to identifying the causes of unemployment and the challenges it faces. To achieve the purpose of the study, the study relied on the descriptive analytical approach by following the qualitative method to conduct (7) interviews with the concerned authorities in the subject of the study, and on the quantitative method in distributing (150) questionnaires to citizens. In the end, the study found that there is great interest on the Palestinian side with regard to combating unemployment, and this was evident through the presence of policies and strategies issued by the competent authorities in combating unemployment, but these policies are based on an unrealistic premise, as it has an imaginary dimension more than practical. The study also showed that the effectiveness and adequacy of government policies affect the fight against unemployment to a low degree. Based on this, the most prominent recommendations were the necessity of working to strengthen the governmental policies concerned with combating unemployment in Palestine and making them more realistic and applicable. The need to put in place governmental policies that limit nepotism and favouritism in employment, and policies that place employment based on competence rather than seniority, and finally put the right person in the right place, and work to increase projects related to helping unemployed people.